1995
DOI: 10.1152/ajprenal.1995.269.1.f110
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II regulates nephrogenesis and renal vascular development

Abstract: To test the hypothesis that angiotensin II (ANG II) is necessary for normal embryonic and postnatal kidney development, the effect of angiotensin receptor blockade or angiotensin converting enzyme inhibition on nephrovascular development was studied in newborn Sprague-Dawley rats and in Rana catesbeiana tadpoles undergoing prometamorphosis. Blockade of ANG II type 1 receptor (AT1) in newborn rats induced an arrest in nephrovascular maturation and renal growth, resulting in altered kidney architecture, characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
189
0
8

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(215 citation statements)
references
References 0 publications
18
189
0
8
Order By: Relevance
“…Interestingly, inhibition of angiotensin generation in rana catesbiana tadpoles undergoing prometamorphosis results in even more marked renal abnormalities with persistence of pronephric tubes and areas of undifferentiated mesenchyme. 49 These experiments, as well as those of other investigators, indicate that not only is angiotensin II necessary for nephrovascular development but also its vascular growth actions are conserved across the phylogenetic scale. 49 In agreement with those findings, deletion of any of the genes of the renin-angiotensin system (angiotensin-converting enzyme, renin, angiotensinogen, and AT1AϩB) results in similar abnormalities ( Figure 6).…”
Section: Renin-angiotensin In Kidney Vascular Developmentmentioning
confidence: 56%
See 1 more Smart Citation
“…Interestingly, inhibition of angiotensin generation in rana catesbiana tadpoles undergoing prometamorphosis results in even more marked renal abnormalities with persistence of pronephric tubes and areas of undifferentiated mesenchyme. 49 These experiments, as well as those of other investigators, indicate that not only is angiotensin II necessary for nephrovascular development but also its vascular growth actions are conserved across the phylogenetic scale. 49 In agreement with those findings, deletion of any of the genes of the renin-angiotensin system (angiotensin-converting enzyme, renin, angiotensinogen, and AT1AϩB) results in similar abnormalities ( Figure 6).…”
Section: Renin-angiotensin In Kidney Vascular Developmentmentioning
confidence: 56%
“…49 These experiments, as well as those of other investigators, indicate that not only is angiotensin II necessary for nephrovascular development but also its vascular growth actions are conserved across the phylogenetic scale. 49 In agreement with those findings, deletion of any of the genes of the renin-angiotensin system (angiotensin-converting enzyme, renin, angiotensinogen, and AT1AϩB) results in similar abnormalities ( Figure 6). The growth effects of angiotensin II are not limited to the renal arterioles and extend to the postglomerular circulation.…”
Section: Renin-angiotensin In Kidney Vascular Developmentmentioning
confidence: 56%
“…The role of the RAS in altered renal development has received considerable attention. Angiotensin II is known to be important in normal renal development (109,110), and variations in dietary protein can alter the RAS (111). In the rat low-protein model, we have shown that renal tissue renin protein and mRNA, AT1R protein and mRNA, and angiotensin II levels are reduced in the newborn and young offspring compared with controls (16,19,97).…”
Section: Targets Of Programming In the Fetusmentioning
confidence: 99%
“…Administration of ACEinhibitors in hypertensive women during pregnancy results in severe malformations in the fetus, including kidney anomalies (48,49). Similar histological changes were also found in several animal models using pharmacological Ang II inhibitors (50,51). Moreover, the ACE inhibitor suppresses glomerular growth in maturing rats (52).…”
Section: Rasis a Regulator Of Fluid Balancementioning
confidence: 68%